Fundamentals of Common Stock Pricing: Evidence from Commercial Banks of Nepal - Karki, Dipendra (NCC Journal, 2018)
This study relates cross-sectional differences in stock prices of Nepalese commercial banks to the underlying behavior of six fundamental variables: earnings per share, book value per share, cash dividend per share, stock dividend per share, price earnings ratio, and firm size. This study uses secondary sources of data. The balanced panel data from commercial banks including 150 observations are used for the period of 2000-2014. The earnings per share and stock dividend per share are the more significant determinants of stock prices of commercial banks in Nepal. The performance of the stock dividend is especially noteworthy; this variable is statistically and economically the most important of the six fundamental variables investigated. NCC Journal Vol. 3, No. 1, 2018, page: 44-64